2003
DOI: 10.1007/s00421-002-0766-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inducing physiological hyperglucagonemia on metabolic responses to exercise

Abstract: The purpose of the present study was to assess the effects of exogenously increasing the circulating levels of glucagon on the metabolic responses to exercise in rats. A total of six groups of rats were infused (iv) either with glucagon (20 or 50 ng x kg(-1) x min(-1)) or saline (0.9% NaCl), either in the resting state or during a bout of running exercise (45 min, 26 m x min(-1), 0% grade). Blood samples were taken at the end of the 45-min experiment. Animals infused with glucagon at 50 ng x kg(-1) x min(-1) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This suggests that glucagon may play an important role in causing hyperglycaemia and, therefore, may contribute to increased insulin resistance in early Type 2 diabetes [2,31]. Indeed, many previous studies in humans or animals have demonstrated that glucagon administration for several hours or days was associated with or without increased fasting blood glucose levels and impaired glucose tolerance [11][12][13]. However, it has been very complicated to determine whether glucagon plays a direct role in these responses, because it is difficult to infuse glucagon to induce hyperglucagonaemia and then block its effects with its receptor antagonist [Des-His 1 -Glu 9 ]glucagon in human subjects for weeks or months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that glucagon may play an important role in causing hyperglycaemia and, therefore, may contribute to increased insulin resistance in early Type 2 diabetes [2,31]. Indeed, many previous studies in humans or animals have demonstrated that glucagon administration for several hours or days was associated with or without increased fasting blood glucose levels and impaired glucose tolerance [11][12][13]. However, it has been very complicated to determine whether glucagon plays a direct role in these responses, because it is difficult to infuse glucagon to induce hyperglucagonaemia and then block its effects with its receptor antagonist [Des-His 1 -Glu 9 ]glucagon in human subjects for weeks or months.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have chronically infused (or injected) glucagon in humans or animals for only a few minutes, hours or days to determine the effects of glucagon on blood glucose levels, serum insulin and glucagon responses, hepatic glucose production and tissue uptake of glucose [6,[11][12][13]. None of these studies have lasted long enough to determine whether long-term hyperglucagonaemia may induce target tissue injury in a human or animal model of Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%